Analyzing the factors that countributed to the decrease of revenue of Pharmaniaga Bhd in Indonesia / Siti Nadirah Aminuddin - Aminuddin, Siti Nadirah (2010)
Unexpected low performance of Pharmaniaga on 2009 did make all of their management unit wonder why it was happened. This situation can be observed through their financial data. The top management was expected that their budget for each year will reach what they had targeted by last year. Surprisingly, what have been targeted are not achieved level that they have expected. Even though Pharmaniaga still recorded high profit for last year in their sales, this giant pharmaceutical company in Malaysia still did not satisfied with their results of sales revenue for last year. One of the factors that focus by this company is the sales revenue in their subsidiary in Indonesia which is known as PT Millennium Pharmacon International (MPI) shows the big declining in their sales. MPI were having confronted with lots of crisis that labeled this comapany as one of Pharmaniaga subsidiaries that contributed to the decrease of the sales of Pharmaniaga Bhd as a whole. However, current economy performance, principal of MPI in Indonesia and competition with local and world giant pharmaceutical company made Pharmaniaga sales unfortunately drop. Due to this circumstances, this issues merit attention from the top management of Pharmaniaga and also all their competitors in Malaysia. This paper present the factors that contributed to the decreasing of the sales of Pharmaniaga Bhd in Indonesia and determine what the strategies that could be consider in order to overcome the problem and remain successful in future.